Fatigue analysis of aluminum components in powertrain mounts - Bergquist, Caroline; Vaez Mahdavi, Elina (My University, 2019)
Components in the powertrain mounts systems withstand a large number of load cycles with varying amplitude during their operational life. Despite this, no fatigue analysis has previously been carried out of the studied components. The main aim of this study was therefore to create a method for analyzing fatigue in aluminum components in powertrain mounts. A bracket in the powertrain mounts system made of high pressure die cast aluminum EN– 46000 was in focus. The study partially aimed to account for and determine the effect of pretension on the bracket fatigue resistance. A widespread problem with fatigue analysis is the access to material fatigue parameters, and approximated material data are often employed. To investigate the consequences the influence of using various material fatigue parameters for EN– 46000 was investigated. Based on a literature study, a strain-based approach to fatigue was selected. This allows to account for plasticity. The construction of strain – life curve combined with the establishment of a Ramberg – Osgood equation for cyclic stress – strain relationship was the basis of the fatigue analysis. Due to the mean stress that arose from the pretension, a mean stress correction following Smith –Watson –Topper was utilized. To decrease computational time, a linear elastic stress FE-analysis was carried out, Neuber correction was employed to account for local plasticity in the fatigue analyses. Fatigue analyses of the bracket were performed with approximated material fatigue parameters using the Bäumel – Seeger method. The bracket was predicted to sustain an infinite number of load cycles. An investigation of how much larger the loads could be to sustain 4 standard operational lives was conducted. The result was 2.4 times the applied load. It was also found that small areas were affected by fatigue. Fatigue analyses were carried out with and without the pretension. A slight decrease in fatigue life was obtained without pretension due to compressive mean stresses. From a sensitivity analysis, it was concluded that employed material fatigue parameters have a significant impact on fatigue life, and that approximated material should not be used for the final fatigue analysis. Keywords:fatigue, aluminum alloys, nCode DesignLife, pretension, strain-based, stress-based, powertrain mounts, material fatigue parameters
Keywords: Transport; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Fastkroppsmekanik; Farkostteknik; Metallurgi och metalliska material; Transport; Sustainable Development; Innovation & Entrepreneurship; Solid mechanics; Vehicle Engineering; Metallurgy and Metallic Materials